The "Strong" and the "Weak" in Romans 14: 1–15:13 and Covid-19-Related Tensions in Christian Congregations The Prospects and Perils of Relating Current Concerns to Sacred Scripture - Stenschke, Christoph W. 1966- (2023)
This essay probes whether (and how) deep differences of opinion concerning the Covid-19 pandemic and the governmental measures set in place to fight it can be related to Paul’s instructions in Romans 14:1-15:8 where he refers to severe conflicts within the Roman congregations. The article describes the nature of the controversy in Romans 14-15 and how it relates to the current socio-cultural context of inner-congregational disputes in the wake of the Covid-19 pandemic. This is followed by a discussion of the hermeneutical challenges of relating Romans 14:1-15:13 to some aspects of the Covid-19 pandemic. Further sections relate text and context, address neglected aspects in Romans 14:1-15:13 and the need for additional perspectives. The article discusses in detail the hermeneutical challenges involved in applying this ancient text to the current situation where the contended issues concern not only "opinions" but also established medical facts.